Cornwall-Norton model in the strong-coupling regime - Natale, A. A. [UNESP] (American Physical Society (APS), 1991)
The Cornwall-Norton model is studied in the strong-coupling regime. It is shown that the fermionic self-energy at large momenta behaves as (p)(m2p)ln(pm). We verify that in the strong-coupling phase the dynamically generated masses of gauge and scalar bosons are of the same order, and the essential features of the model remain intact. © 1991 The American Physical Society.